Origami & other paper creations - Descamps, Ghylenn (Tunbridge Wells, Kent Search Press, 2013)
It combines the traditional aspects of the art form with contemporary, practical uses such as stationery, jewelry, and modern decoration. Projects range from bookmarks and table decorations to holiday activities, and easy-to-follow instructions, detailed diagrams, templates, and colour photographs are included
Arts (Papercrafts)
Translation of: Origami & créations en papier
1 2 13 14
Keywords: Origami; Paper work